Two new species of Pseudoniphargus (Amphipoda: Pseudoniphargidae) from southern Spain - Stokkan, Morten; Pérez-Fernández, Antonio; Baena, Manuel; Jaume, Damià (Zootaxa, 2018)
Two new species of subterranean water amphipod crustaceans of the genus Pseudoniphargus (Pseudoniphargidae) are described from gypsum caves of Andalusia, southern Spain. Both species share the extreme elongation of the male third uropod, a striking feature frequently reported in the genus and that seems to have arisen independently in several lineages. These findings raise the number of species of Pseudoniphargus known from the area to 17.